2015
DOI: 10.1002/pbc.25781
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Retinoblastoma: A Cross‐Sectional Study of 122 Survivors from India

Abstract: We found a significantly poorer QOL in retinoblastoma survivors with the psychosocial health domain being more affected than the physical domain. Age less than 18 months at diagnosis predicted better QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
4
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 18 publications
2
50
4
3
Order By: Relevance
“…12 An Indian study reported that because of differences in the medical and social support systems of pediatric patients with RB from those in Western societies, the differences in scores of the social and school dimensions between pediatric patients and the control group were statistically significant. 13 In our study, only the school dimension score in the PedsQL TM 4.0 of pediatric patients in the younger age group (5-7 years) was significantly lower than that of normal children, whereas the differences in scores of the social and school dimensions in the PedsQL TM 4.0 for 8-18-year-old children between the study group and the normal control group were both statistically significant. It has been shown that when the survival time of pediatric patients with cancer is longer, the quality of life is worse.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…12 An Indian study reported that because of differences in the medical and social support systems of pediatric patients with RB from those in Western societies, the differences in scores of the social and school dimensions between pediatric patients and the control group were statistically significant. 13 In our study, only the school dimension score in the PedsQL TM 4.0 of pediatric patients in the younger age group (5-7 years) was significantly lower than that of normal children, whereas the differences in scores of the social and school dimensions in the PedsQL TM 4.0 for 8-18-year-old children between the study group and the normal control group were both statistically significant. It has been shown that when the survival time of pediatric patients with cancer is longer, the quality of life is worse.…”
Section: Discussioncontrasting
confidence: 56%
“…The differences in these results were greater than those in the Indian study, which showed that the differences in quality of life between pediatric patients with unilateral and bilateral RB were not statistically significant. 13 In this study, the quality of life scores of pediatric patients with diagnosis ages ≤ 18 months were better than those of patients with diagnosis ages > 18 months. Some evidence has indicated that older diagnosis ages of pediatric patients with cancer are associated with more physiological and psychological problems in long-term cancer survivors.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…3 Despite the high cure rates, retinoblastoma survivors tend to have a poorer quality of life and have greater school absenteeism. 4 Further, pediatric cases of heritable retinoblastoma have an elevated risk for developing sarcoma and leukemia by age 14. 5 In adulthood, these children have an increased risk of chronic medical conditions including a second malignant neoplasm.…”
Section: Introductionmentioning
confidence: 99%